THE EFFECT OF THE IMPLEMENTATION OF INFORMATION TECHNOLOGY (E-SYSTEM) ON TAXPAYER COMPLIANCE WITH THE USE OF TECHNOLOGY AS MODERATION VARIABLES IN KPP PRATAMA MAKASSAR UTARA - Fatimah Hidayahni; Tenriwaru Tenriwaru; Fadlia Nasaruddin (JOSAR (Journal of Students Academic Research), 2019)
This study aims to examine the effect of the application of information technology (e-system) on tax compliance with the use of technology as a moderating variable at KPP Pratama Makassar Utara. The sample in this study was taxpayers who were registered at KPP Pratama Makassar Utara. This study uses primary data, direct research by giving questionnaires to respondents. The data analysis method uses the smart PLS approach to test the effect of the application of information technology (e-system) on taxpayer compliance with the use of technology as a moderating variable. The analytical method used is simple linear regression analysis. The results showed the application of information technology had a positive and significant effect on taxpayer compliance. The application of information technology has a positive and significant effect on taxpayer compliance by being moderated by the use of technology.